Aplikasi Pemesanan Jadwal Pengobatan Tradisional Pada Startup Medis Reborn Berbasis Web - Dinary Dwihatami; Suendri Suendri; Raissa Amanda Putri (Journal of Information System Research (JOSH), 2022)
Health services at traditional medicine clinics have problems, namely the absence of an online treatment schedule ordering system that makes customers have to take treatment and customers must directly register at the clinic for treatment and often queue for a long time to get the desired treatment. This research aims to design and build a traditional medicine application on a web-based startup Medis Reborn. The system development method used is the waterfall method. The result of the research is the creation of a traditional medicine application, which is an online platform that connects traditional medicine clinics with customers in one place using a website so that customers can order traditional medicine schedules online. This online ordering system provides treatment scheduling as well as a choice of information on the location of the nearest clinic.